2013
DOI: 10.1161/circresaha.113.301814
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Excitation of Vasopressin Neurons

Abstract: Rationale: Increased arginine-vasopressin (AVP) secretion is a key physiological response to hyperosmotic stress and may be part of the mechanism by which high-salt diets induce or exacerbate hypertension. Objective: Using deoxycorticosterone acetate-salt hypertension model rats, we sought to test the hypothesis that changes in GABA A receptor–mediated inhibition in AVP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…In agreement with these observations, a previous study reported that the value of E GABA measured by perforated patch recording in VP MNCs in vitro lies below the threshold for action potential discharge (Kim et al, 2013). However, this result is contradicted by another study reporting that E GABA is depolarized in VP MNCs and that GABA excites these neurons in hypothalamic slices under control conditions (Haam et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In agreement with these observations, a previous study reported that the value of E GABA measured by perforated patch recording in VP MNCs in vitro lies below the threshold for action potential discharge (Kim et al, 2013). However, this result is contradicted by another study reporting that E GABA is depolarized in VP MNCs and that GABA excites these neurons in hypothalamic slices under control conditions (Haam et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…However, a recent study has shown that rat MNCs display a collapse in the transmembrane chloride (Cl − ) gradient required for inhibitory GABA A R signaling after chronic salt loading (Kim et al, 2011). A similar effect can be induced by a high-salt diet in uni-nephrectomized rats treated with deoxycorticosterone acetate (DOCA), where a weakening of BR-mediated inhibition is also associated with a VP-dependent increase in BP (Kim et al, 2013). These observations indicate that plastic changes in the BR-mediated control of MNCs can allow these cells to participate in the regulation of BP.…”
Section: Introductionmentioning
confidence: 92%
“…51 It was recently reported that g-aminobutyric acid-ergic excitation of vasopressin neurons in the supraoptic nucleus is a critical mechanism underlying sodium-dependent hypertension. 52 Therefore, additional study is warranted to assess if klotho deficiency promotes AVP synthesis and release in response to HS, which could contribute to the development of klotho deficiency-induced salt-dependent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, the available data are not conclusive regarding the manner in which multimerization affects CCC functions 6,42,44 . CCCs are expressed in all organ systems and, in addition to being instrumental in neuronal signalling, they are involved in a range of physiological processes, including cell volume regulation (BOX 1), transepithelial ion transport, neuroendocrine signalling and blood pressure regulation 6,7,33,4548 .…”
Section: Expression Of Cccs In the Cnsmentioning
confidence: 99%
“…Strongly depolarizing GABAergic synaptic responses can be functionally excitatory, and they are termed ‘GABA PSPs’. Such responses are based on a high [Cl − ] i , and they are mainly seen in immature or diseased neurons 40,48,165168 .…”
Section: Cccs Regulate Inhibitory Signallingmentioning
confidence: 99%